Wisata Sejarah Kerajaan Berbasis Masyarakat dalam Meningkatkan Perekonomian Masyarakat di Kota Karangasem Taman Soekasad Bali - Riza Dewi Al Ardi (Jurnal Al-Tatwir, 2021)
The tourism industry is one of the fields that is able to accelerate economic movement in a region, so that it may accelerate regional growth and development. One of the benefits of the tourism industry is at least able to improve the economic level of the tourism region community. The current study discusses how Soekasada Park becomes a tourist attraction that can improve the economy of the people of Karangasem, Bali. The current study is a qualitative research which research method is used to examine the condition of a natural object, namely Soekasada Park, in Karangasem, Bali. In order to increase the community's income and to empower the community, the park owner has allowed the community to sell stuff outside the park area, although, since the arrival of the COVID-19 outbreak, people's income has begun to decline due to the lack of visitors. The amount of income the community could reach before Covid was around 11,000,000-66,000,000 per year while the results from the park itself could reach 1-3 billion. From the discussion above, it can be perceived that the Soekasada Park in Karangasem, Bali is a historical tourist attraction that can provide an increase in the community's economy and reduce poverty.